Comparative Study of Single Dose Epidural Morphine and Intermittent Dose Morphine with Bupivacaine in Post Cesarean Analgesia - Agarwal, K; Sharma, M; Agarwal, N; Agrawal, VK; Agarwal, A (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: Obstetric anesthesia presents a challenge to the anesthesiologist. The effective pain management allows the parturient adequate degree of comfort and promotes physical recovery and a sense of well being. Methods: This randomized controlled study was designed to assess the analgesic efficacy and side effects of single dose direct epidural morphine (Group 1) versus intermittent 12 hourly epidural morphine with bupivacaine (Group2) for postoperative analgesia in lower segment caesarean section cases. Results: Each group consisted of 36 patients. Demographic characteristics of two groups were comparable and differences among them were not statistically significant. Mean duration of analgesia was significantly longer in group one patients (16.5 ± 2.5) in comparison to group two patients (11.5 ± 1.5). Mean highest visual analogue scales (VAS scale) was significantly lower (3.2± 0.9) in group one patients in comparison of group two (6.7±0.8) patients. Only 43% patient in group one required supplementary analgesic (Inj Paracetamole/ Diclofenac) and 71% required Inj epidural Morphine / Inj bupivacaine in group two. Mean number of supplementary analgesic required in group one was 0.7 and it was 1.8 in group two. There was no significant difference in nausea, vomiting, itching and pruritis in two groups of patients. Conclusions: our study showed that the use of single dose epidural morphine was associated with lower pain scores at rest and movement when compared to intermittent epidural morphine with bupivacaine in post-caesarean section analgesia. Single dose epidural morphine was found more convenient, less cumbersome and less costly as compared to intermittent epidural morphine for post-caesarean section analgesia. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 41-44 DOI: http://dx.doi.org/10.3126/njog.v7i1.8835